Does a 1-year age gap modify the influence of age, maturation, and anthropometric parameters as determinants of performance among youth elite soccer players? - Bidaurrazaga-Letona, I.; Lekue, J. A.; Amado, M.; Gil, S. M. (The Journal of Strength and Conditioning Research, 2019)
Because age-groups in soccer often comprise children born within a 2-year time frame, characteristics that define the profile of a successful player may not be appropriate for the oldest or youngest players of the same age-group. Therefore, this study aimed to determine to what extent performance was influenced by age, maturation, and body size in elite soccer players with barely 1-year age gap. Anthropometry, 15-m sprint test, modified Barrow's agility test, Yo-Yo intermittent recovery test level 1, countermovement jump, and handgrip test were conducted in players aged 12 years and under (n = 82; age, 11.1 ± 0.6 years) and between 12 and 13 years (n = 79; age, 12.8 ± 0.6 years). A total score of performance, chronological age, and age at peak height velocity were calculated. Descriptive statistics, Student's t-tests, and multiple linear regressions were performed. The explained variance in composite score was greater in the older (54%) than in the younger (30%) players. Sum of skinfolds was the primary predictor of 15-m sprint and countermovement jump in the younger group, whereas in the older group, chronological age and body size appeared as predictors of performance (41%). Body size explained the variance in most tests in older players. In the younger group, biological maturity status explained the variance in endurance (35%) and handgrip (59%) tests. In summary, chronological age and sum of skinfolds influenced the most tests; however, predictors differed between age groups. These findings highlight the importance of assessing individual differences in young male soccer players regardless of their similarity in age.